Basic Content Analysis Journalism Training for Islamic Communication and Broadcasting Students at UIN Sunan Kalijaga Yogyakarta - Latif Syaipudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This basic content analysis-based journalism training was held for fourth-semester students of the Islamic Communication and Broadcasting (KPI) Study Program at UIN Sunan Kalijaga Yogyakarta to support the learning outcomes of the Fundamentals of Journalism course taught by M. Sinung Restendy, M.Si. The main objective of the training was to improve students' theoretical understanding and practical skills in analyzing media content critically and systematically. The training method combined theoretical approaches, case studies, and direct practice using online news from national media. Evaluation results showed a significant increase in understanding the concept of content analysis, identification of media framing, and awareness of ideological bias in reporting. This training was based on mass communication theory (McQuail), content analysis (Krippendorff), framing (Goffman and Eriyanto), and agenda setting theory (McCombs & Shaw). The findings showed that the training was able to shape students' critical attitudes as prospective ethical and responsible journalists. Therefore, this activity is recommended to be a sustainable program with the development of more in-depth advanced materials and an approach based on Islamic values. This training has made a real contribution to strengthening media literacy and journalistic competence of KPI students.